The nature of learning tasks and knowledge acquisition:The role of cognitive engagement in physical education - Wang, Yubing (Eur Phy Educ Rev, 2017)
Acquiring scientific knowledge about physical activity is necessary for students to become physically literate for life, and cognitive engagement and cognitive levels of tasks are two components that often determine the effectiveness of knowledge acquisition. This study sought to determine the extent to which students’ cognitive engagement in descriptive, relational and reasoning learning tasks contributed to their acquisition of knowledge and the extent to which cognitive engagement on lower-level tasks contributed to higher-level tasks (e.g. descriptive to relational to reasoning). The performance of students in descriptive, relational and reasoning tasks and knowledge acquisition was measured in 992 middle school students in active physical education lessons. The results revealed that students’ performance in relational (regression coefficient 0.09, p < 0.01) and reasoning (regression coefficient = 0.06, p < 0.01) tasks directly contributed to their acquisition of knowledge (R(2) = 0.14). The performance of students in descriptive tasks indirectly contributed to knowledge acquisition through influencing their performance in relational and reasoning tasks (indirect effect = 0.09, p < 0.01).